2009
DOI: 10.3109/08820530903389775
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Combination of Triamcinolone Acetonide and Bevacizumab (Kenacort-Avastin) in Diffuse Diabetic Macular Edema

Abstract: Intravitreal combination of Triamcinolone Acetonide and Bevacizumab seems to be effective in improving visual acuity and macular edema in patients with diabetic maculopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…21 Tsilimbaris MK et al found out major decrease in central macular thickness and superior best corrected visual acuity in group with combined IVB-IVTA and showed this therapy to be very effective. 22 In all of these studies, results are comparable to our study supporting combined simultaneous use of bevacizumab with corticosteroids to be more favorable with better outcomes.…”
Section: Discussionsupporting
confidence: 85%
“…21 Tsilimbaris MK et al found out major decrease in central macular thickness and superior best corrected visual acuity in group with combined IVB-IVTA and showed this therapy to be very effective. 22 In all of these studies, results are comparable to our study supporting combined simultaneous use of bevacizumab with corticosteroids to be more favorable with better outcomes.…”
Section: Discussionsupporting
confidence: 85%
“…The quantitative predictions, with forecasting over a relatively short time, open opportunities for the eventual prevention of the development of the first signs of retinal vascular diabetic retinopathy and sight‐threatening retinal oedema. There are numerous recent experimental treatments of advanced diabetic retinopathy, such as injections of steroids and anti‐vascular endothelial growth factor agents, which have been successful in some patients 46,47 . The most recent studies suggest that a combination of these treatments might be even more effective in reducing visual loss but a preventative measure that is less invasive is still needed for diabetic patients 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Before the administration of the drugs, the IOP was 15.6 ± 2.3 (range 11-20) mmHg in the STTA-treated eyes and 15.7 ± 2.8 (range [11][12][13][14][15][16][17][18][19][20] mmHg in the control eyes, and there was no significant difference between them (P = 0.927). After the initial IVB injection, the IOP in the STTA-treated eyes increased steeply and, after 24 weeks, significantly increased, while the IOP in the control eyes b Reduction ratio (refer to the text) in eyes with (black bar) and without (white bar) STTA.…”
Section: Alteration Of Iopmentioning
confidence: 63%
“…A significant difference was found between the 2 groups (P = 0.008) Reduction in the frequency of intravitreal bevacizumab administrations achieved by posterior… with IVTA and bevacizumab, and the authors concluded that IVTA/IVB induced earlier functional and morphological regression than did IVB, although the prognoses did not differ significantly between IVTA/IVB and IVB [17,18]. Although the efficacy of combined IVTA/IVB for DME was reported [19], the beneficial inferiority of IVTA/ IVB to IVB owing to treatment complications was also pointed out [20,21].…”
Section: Discussionmentioning
confidence: 86%